2011
DOI: 10.1097/shk.0b013e3181facf73
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Berberine and Yohimbine Protects Against LPS-Induced Myocardial Dysfunction Via Inhibition of Cardiac I-κBα Phosphorylation and Apoptosis in Mice

Abstract: Myocardial dysfunction is a common complication in sepsis and significantly contributes to the mortality of patients with septic shock. Our previous study demonstrated that pretreatment with berberine (Ber) protected against the lethality induced by LPS, which was enhanced by yohimbine, an [alpha]2-adrenergic receptor antagonist, and Ber combined with yohimbine also improved survival in mice subjected to cecal ligation and puncture. However, no studies have examined whether Ber and yohimbine reduce LPS-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…However, there is no investigation concerning the effect of Ber on DOX-triggered cardiomyocyte apoptosis. Our previous study has showed that Ber attenuates myocardial apoptosis and cardiac dysfunction in endotoxemic mice [17]. Thus, we hypothesized Ber could inhibit DOX-induced cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, there is no investigation concerning the effect of Ber on DOX-triggered cardiomyocyte apoptosis. Our previous study has showed that Ber attenuates myocardial apoptosis and cardiac dysfunction in endotoxemic mice [17]. Thus, we hypothesized Ber could inhibit DOX-induced cardiomyocyte apoptosis.…”
Section: Introductionmentioning
confidence: 86%
“…In separate experiments, rats were treated as described above, but a single dose of Ber (60 mg/kg) was used. Then, the cardiac function was assessed at 84 h after DOX administration with VisualSonics R Vevo770™ High-Resolution In Vivo Imagine System ((VisualSonics Inc., Toronto, Ontario, Canada) as described previously [17]. After echocardiographic assessment, the rats were immediately anesthetized with pentobarbital sodium (50 mg/kg, intraperitoneally) and morphine hydrochloride (50 mg/kg, subcutaneously), the adequacy of the anesthesia was monitored by disappearance of the corneal reflex, loss of the pedal reflex and failure to respond to a skin incision.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, we demonstrate that Y does not enhance the protective effects of Ber against intestinal damage that is caused by treatment with LPS. It has been reported that pretreatment with Y once a day for 3 days prevents LPS-induced myocardial dysfunction in mice [24] . Thus, the enhanced protection of Ber against endotoxemia by Y may be related to the improvement of LPS-induced myocardial dysfunction in mice that are pretreated with Y.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both Rhy and yohimbine belong to the indole alkaloid, and have similar chemical structure [11]. Our recent study showed that pretreatment with yohimbine prevented myocardial dysfunction in mice challenged with lipopolysaccharide (LPS), which has been implicated as one of the major causes of Gram-negative bacteria-induced sepsis [12]. Based on these findings, we hypothesize that Rhy has a protective effect on LPS-induced cardiac dysfunction.…”
Section: Introductionmentioning
confidence: 95%